-8a+6a+42=1

Simple and best practice solution for -8a+6a+42=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8a+6a+42=1 equation:


Simplifying
-8a + 6a + 42 = 1

Reorder the terms:
42 + -8a + 6a = 1

Combine like terms: -8a + 6a = -2a
42 + -2a = 1

Solving
42 + -2a = 1

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-42' to each side of the equation.
42 + -42 + -2a = 1 + -42

Combine like terms: 42 + -42 = 0
0 + -2a = 1 + -42
-2a = 1 + -42

Combine like terms: 1 + -42 = -41
-2a = -41

Divide each side by '-2'.
a = 20.5

Simplifying
a = 20.5

See similar equations:

| 4x-3(x-1)=-4+3x+11 | | Fx=10x^2+8x+8 | | 22/2= | | 3x(x^2+2x-6)+4(x^2-6x+2)= | | g(x)=3.4x-8 | | 20n=10n^2 | | 2.2m=19.8 | | 13x+5=-35 | | 6=2(v+8)-4v | | 4(6y+1)+8=6(2y+5)-5 | | 0.9(5x+15)2.5-(x+3)= | | x^6+8y^3= | | (12y^3)+(24y^2)=3y+6 | | X+2x+(2x+30)=280 | | -x=4x-3 | | 4+3x-2=8x+18-3x | | -8=-8(2x-7) | | 93=(93)(63) | | st+3y=6 | | 8-3(1-3m)= | | 1.8+7n=9.5-4bn | | 0.60p+80=0.70+30 | | 2(6x-2)=3(5x-5) | | 6y^2+1y-2=0 | | Y=157.5x+50 | | 0.8y=-4 | | [-5/8][-8/15]= | | 1=-1.5+0.5y | | x^4-5x^3-9x^2+45x= | | 1/2+(2/3)(3/4)-(4/5)(5/6)= | | 1/2+(2/33/4)-(4/5)(5/6)= | | -2(7x-1)=-5(3x-1) |

Equations solver categories